The impact of COVID-19 on Italian accommodation: A supply-perspective - Giacomo Del Chiappa; Ilenia Bregoli; Anestis K. Fotiadis (Journal of Tourism, Heritage & Services Marketing, 2021)
Purpose: The current COVID-19 pandemic has created an extremely dynamic and uncertain environment in which businesses find it very difficult to operate, particularly those in the hospitality industry. It is therefore very important to understand which actions hospitality businesses think the private and public sectors should adopt in order to cope with the pandemic and its impact. To facilitate this, this research adopted chaos theory to investigate Italian small and medium enterprises (SMEs) in the hospitality sector. Methods: A mixed method approach, based on a convergent parallel design data validation variant, was adopted. A survey with open and closed questions was developed and sent to a sample of businesses. 1,040 completed questionnaires were collected and analysed through descriptive statistics; in addition to these usable surveys, 361 open-ended answers were analysed thematically. Results: The results showed that Italian entrepreneurs and managers were over-relying on interventions from the public sector and that there was a lack of business actions being made, thus evidencing a deficit in terms of long-term strategic thinking and the innovation required during such turbulent times. Implications: Although these results cannot be generalised to the whole of the hospitality industry, they shed light on important elements that industry associations should take into account.
Keywords: H12; I15; L83; 330; chaos theory; COVID-19; accommodation sector; convergent parallel design; Italy; mixed method